Electron-transfer properties of an efficient nonheme iron oxidation catalyst with a tetradentate bispidine ligand - Comba, Peter; Fukuzumi, Shunichi; Kotani, Hiroaki; Wunderlich, Steffen (Angewandte Chemie. International edition, 2010)
The oxidation catalyst [(L)FeIVO] (see picture; L is a tetradentate bispidine ligand) has the highest known one-electron reduction potential for a FeIVO species (0.73 V vs. SCE). Investigations into the electron-transfer kinetics show a linear correlation with the bond dissociation energy of the organic substrates.
Gesehen am 26.05.2023